Growth status, curd yield and crop duration of late season cauliflower varieties - Giri, Hom Nath; Sharma, Moha Dutta; Thapa, Resham Bahadur; Pande, Keshab Raj; Khatri, Bhim Bahadur (Journal of Agriculture and Natural Resources, 2020)
Cauliflower is an important winter season vegetable crop having year-round demand in Nepal. Due to longer crop duration in late winter season, there was a production of poor-quality curds and lower yield faced by the farmers in Terai region of Nepal. An experiment was conducted to identify the short duration late season varieties at Rampur, Chitwan Nepal during November 2016 to March, 2017. These varieties were Freedom, Titan, Ravella, Amazing, Artica, Bishop, Casper, Indam 9803 and NS 106 (introduced from USA, Europe and India), and Snow Mystique and Snowball 16 (introduced from Japan). The experiment was laid out in Randomized Complete Block Design (RCBD) with four replications. The highest plant height (71.9 cm) and canopy diameter (74.5 cm) at last harvest of cauliflower was mostly produced by Titan followed by NS 106, Snow Mystique, Bishop and Indam 9803. Similarly, significantly shorter period for final curd initiation of 65 days after transplanting was observed in Freedom and shorter period for final curd maturation of 77 days after transplanting was also recorded in Freedom than other varieties. Significantly, higher curd yield of 54.8 t/ha was produced by Bishop than other varieties. In conclusion, Bishop was the best hybrid variety while other suitable varieties were NS 106, Titan, Artica and Snow Mystique for better growth and higher curd yield in Chitwan condition. Similarly, Freedom was identified as short duration varieties which can minimize the negative effects in late winter season due to higher temperature.